The Influence of Pituitary Morphology on the Occurrence of Hormonal Disorders in Patients with Empty Sella or Partial Empty Sella - Bernadetta Kałuża; Mariusz Furmanek; Jan Domański; Aleksandra Żuk-Łapan; Emilia Babula; Iga Poprawa; Małgorzata Landowska; Karolina Jarząbek; Justyna Popczyńska; Paulina Filipowicz; Małgorzata Wielgolewska; Jerzy Walecki; et al. (Biomedicines)
Background/Objectives: The aim of the study was to prospectively assess the impact of certain parameters of pituitary morphology assessed with the use of magnetic resonance imaging on the occurrence of hormonal disorders in patients with primary partial empty sella (PES) or primary empty sella (ES). Methods: Forty-three patients were divided into two groups: group 1—patients with PES (n = 20); group 2—patients with ES (n = 23). Results: Patients with ES were characterized by larger both the transverse (14.8 ± 2.9 mm vs. 17.2 ± 2.9 mm, p = 0.016) and anteroposterior (AP) diameters of the pituitary (11.4 ± 1.4 mm vs. 13.2 ± 1.9 mm, p = 0.003), a smaller craniocaudal (CC) diameter (3.9 ± 0.62 mm vs. 2.2 ± 0.6 mm, p = 0.001), and a lower pituitary volume (332.8 ± 107.6 mm3 vs. 243.5 ± 70.9 mm3, p = 0.001). Moreover, an AP infundibular displacement was more common in patients with ES (7 [35%] vs. 16 [69.6%]., p = 0.023). Despite the fact that secondary adrenocortical insufficiency was shown to be significantly more common and ACTH levels to be significantly lower (27.5 ± 13.2 pg/mL vs. 21.8 ± 17.6 pg/mL, p = 0.039) in patients with ES (0 [0%] vs. 3 [13.4%], p = 0.046), univariate logistic regression did not reveal any significant associations of pituitary diameters, pituitary volume, or pituitary stalk displacement with endocrine disorders, such as secondary adrenocortical insufficiency or hyperprolactinemia, which was confirmed with multivariate logistic regression adjusted for age, sex, BMI, and arterial hypertension. Conclusions: Radiologically assessed CC, AP, and transverse pituitary diameters, pituitary volume, or pituitary stalk displacement in patients with PES or ES have no bearing on the rates of hormonal disorders. Nonetheless, certain hormonal disorders may be more common in patients with ES, which suggests a need for hormone-level assessments in this population.